FETAL SYNDROMES - DIAGNOSIS AND MANAGEMENT USING 3D-4D SONOGRAPHY - Kurjak, Asim (Scripta Medica, 2019)
Three-dimensional ultrasound (3D US) has become a very powerful and progresively popular ultrasound technique in the last three decades (1989-2019).1 Today, it is used in regular prenatal assessment in everyday clinical practice as additional method to two-dimensional ultrasound (2D US). Over the time, 3D US equipment and technology dramatically enhanced the qality of images, shortened the time of acquisition, and at the same time improved our ability to assess and visualize the normal and to detect abnormal development of a embryo and fetus in utero.1-13 Acquired volumes can be stored, re-loaded and re-evaluated at any time. Different imaging modalities can be applied for more detailed survey. Particular region of interest such as small defects can be displayed in the ideal plane that sometimes can not be achived by conventional 2D US technique.3,4,9,10 This increases the accuracy of the detection and diagnosis of various malformations and fetal syndromes.2 Diagnosing fetal syndromes is a major challenge both in the prenatal and postnatal period.2 The syndrome is like a big puzzle whose parts need to be carefully assembled to get a whole picture.2 Good multidisciplinary approach, proper communication and collaboration with parents and all physician’s involved are required in the diagnostic process. All available resources and tools are needed to increase diagnostic precision in the prenatal diagnosis of fetal syndromes.4 The introduction of highly specialized software systems for three-dimensional and four dimensional ultrasound (3D/ 4D US) enable detailed assessment of the fetal anatomy and the evaluation of the dynamics of structural and functional development of the fetus in real-time.2,4 Owing to this, clinical practice has also gained new functional tests such as the Kurjak’s antenatal neurodevelopmental test (KANET); named in honor of its author; used for the evaluation of fetal brain function.2-4,24-31 Antenatal detection and diagnosis of fetal anomalies and syndromes is shifted from the 2nd to the 1st trimester of pregnancy2,4,10-12 partly due to technological advances and benefits of imaging quality with 3D/4D US technology, as reported by many authors.